2015
DOI: 10.1039/c4ta05676k
|View full text |Cite
|
Sign up to set email alerts
|

Initial decomposition reaction of di-tetrazine-tetroxide (DTTO) from quantum molecular dynamics: implications for a promising energetic material

Abstract: Di-tetrazine-tetroxide (DTTO) was predicted in 2001 to have a density (up to 2.3 g cm À3) and heat of detonation (up to 421.0 kcal mol À1) better than other explosives, making it the "holy grail" of energetic materials (EMs), but all attempts at synthesis have failed. We report Density Functional Theory (DFT) molecular dynamics simulations (DFT-MD) on DTTO crystal for the two most stable monomers. We predict that the most stable isomer (c1) has a density of r ¼ ), a unique initial reaction among EMs. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…We have carried out similar DFT-MD simulations to investigate the initial thermal decomposition reaction of TKX-50 37 and DTTO, 38 which also have been suggested to be insensitive energetic materials. There we found the rst decomposition barrier of TKX-50 (45.1 kcal mol À1 ) and DTTO (45.9 kcal mol À1 ), which are similar to the value we nd for MTO (46.5 kcal mol À1 ) and MTO3N (44.1 kcal mol À1 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have carried out similar DFT-MD simulations to investigate the initial thermal decomposition reaction of TKX-50 37 and DTTO, 38 which also have been suggested to be insensitive energetic materials. There we found the rst decomposition barrier of TKX-50 (45.1 kcal mol À1 ) and DTTO (45.9 kcal mol À1 ), which are similar to the value we nd for MTO (46.5 kcal mol À1 ) and MTO3N (44.1 kcal mol À1 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also found that compounds with higher values of ρ and Q will possess higher values of D and P . These results indicated that ρ and Q may be acted as the most effective influence factor on the values of D and P of the title compounds 29‐31 . Figure 3A presents the influence of different substituents or different bridges on ρ .…”
Section: Introductionmentioning
confidence: 87%
“…Our QMD simulation indicated that the interactions between CH 4 and fragments of O and OH are responsible for the thermal decomposition pf methane molecules through the continuous assaults of O or OH to the carbon atom and its affiliated hydrogen atoms. In addition, in order to obtain detailed chemical reactions information, we heat up the system with a gradually linearly increased temperature from 300 K to above 4000 K. In fact, the chemical reactions would happen at a lower temperature in real experiment than our simulations here due to the long timescale, as discussed by Ye et al 40 The initial decomposition temperature of CH 4 in my QMD simulations is 3480 K which is higher than the experimental measured ame temperature ($1500 K). 14,15 This is due to the extremely high heating rate in our QMD simulations.…”
Section: Reaction Mechanisms At High Temperatures From Qmd Simulationsmentioning
confidence: 93%